The Role of Mesoscale Plasma Sheet Dynamics in Ring Current Formation - Sorathia, K. A.; Michael, A.; Merkin, V.G.; Ukhorskiy, A.Y.; Turner, D. L.; Lyon, J.G.; Garretson, J.; Gkioulidou , M.; Toffoletto, F.R. (Frontiers in Astronomy and Space Sciences, 2021)
During geomagnetically active periods ions are transported from the magnetotail into the inner magnetosphere and accelerated to energies of tens to hundreds of keV. These energetic ions, of mixed composition with the most important species being H+ and O+, become the dominant source of plasma pressure in the inner magnetosphere. Ion transport and acceleration can occur at different spatial and temporal scales ranging from global quasi-steady convection to localized impulsive injection events and may depend on the ion gyroradius. In this study we ascertain the relative importance of mesoscale flow structures and the effects of ion non-adiabaticity on the produced ring current. For this we use: global magnetohydrodynamic (MHD) simulations to generate self-consistent electromagnetic fields under typical driving conditions which exhibit bursty bulk flows (BBFs); and injected test particles, initialized to match the plasma moments of the MHD simulation, and subsequently evolved according to the kinetic equations of motion. We show that the BBFs produced by our simulation reproduce thermodynamic and magnetic statistics from in situ measurements and are numerically robust. Mining the simulation data we create a data set, over a billion points, connecting particle transport to characteristics of the MHD flow. From this we show that mesoscale bubbles, localized depleted entropy regions, and particle gradient drifts are critical for ion transport. Finally we show, using identical particle ensembles with varying mass, that O+ non-adiabaticity creates qualitative differences in energization and spatial distribution while H+ non-adiabaticity has non-negligible implications for loss timescales.